Pelatihan Resiliensi pada Remaja Panti Asuhan - Kimmy Katkar; Purwaningtyastuti Pungky; Retno Ristiasih Utami (Universitas Muhammadiyah Semarang, 2021)
Adolescents who live in orphanages will only have their physiological needs met but not their psychological needs, this is because the condition of the orphanage with the number of caregivers and orphans that are not comparable can cause psychological problems. The lack of guidance from caregivers in more depth can be one of the triggering factors for adolescents who live in orphanages when experiencing problems in their lives to be more susceptible to stress, pressure and depression. This makes it easy for individuals to fall and find it difficult to get back up. The implementation method in this service activity is carried out offline by giving lectures, case studies and games. Activities were evaluated using the pretest and post-test measurement models. Based on the results of the analysis using the Paired Sample T-Test, it was found that there was an increase of 17.98 with a difference in the mean score of pretest 56.95 and post-test 74.93. This shows an increase in resilience in orphaned adolescents after being given training. The activities that have been carried out are very useful for adolescents by increasing resilience and gaining new knowledge which before this activity teenagers did not know the meaning and importance of individuals having high resilience.